Minimize sand production by controlling wellbore geometry and flow rate - Samsuri, Ariffin (2000)
The production of sand particle has become serious problem to oil and gas well and was subject for study during the past years. Basically, sand production must be the results of a change in strength of the formation rock due to drilling, perforation and production operation and drag forces of the produced fluids. Therefore, during designing and developing stages, parameters related to sand production need to be examined carefully. This paper presents an experimental study of the effects of wellbore geometry and flow rate to sand production and total oil recovery; to minimize sand production as well as optimize production. The experimental works include of static and dynamic sand production tests, which were carried out on wellbore models with different wellbore angle, perforation shot density; and perforation pattern and flow rate using Servo Control Compression Testing Machine (SCCTM). The results show that oil production is reduced as sand production increases and most of produced sand are large size indicating the dominant effects of the breakage of cementing materials. Sand production increase significantly after effective stress reaches 35-60% of rock compressive strength and followed by the reduction of total oil recovery to 55-73%. In addition, sand production increases as wellbore angle, shot density, flow rate increase and as perforation pattern change from spiral to inplane and finally inline, especially for model with more than 10o well bore angle, inline pattern and 1600cc/h flow rate. Therefore, in order to optimize production, sand production must be minized by reducing wellbore angle (<10o); shot density, flow rate (<1600cc/h), perforated with spiral pattern and pore pressure should be controlled so that effective stress around a wellbore is not more than 35% of rock compressive strength.